2019
DOI: 10.33021/jaaf.v3i1.679
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh DER, TATO dan NPM Terhadap Kebijakan Dividen (Studi Kasus Pada Industri Dasar dan Kimia yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2012-2016)

Abstract: This research was conducted to examine the effect of Debt to Equity Ratio (DER), Total asset turnover (TATO) dan Net profit margin (NPM) to Dividend Payout Ratio (DPR). The object for this research is basic industry and chamicals listed on the Indonesia Stock Exchange in the period 2012-2016. This research was conducted using quantitative menthod with total 10 sample of research were determined by saturated sampling. Method of hypothesis testing using t-test. This research use Debt to Equity Ratio (X1), Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
4
1
3
Order By: Relevance
“…The higher the total asset turnover ratio of a company, the greater the company's profit, so the amount of dividends to be distributed is also more significant. The research results support the statement's hypotheses by Firdaus and Handayani (2019) and Simanjuntak (2016), which states that total asset turnover positively and significantly affects dividend policy. Collateralizable assets are the number of assets guaranteed by the company to creditors when applying for loans.…”
Section: H2: Investment Opportunity Has a Negative Effect On Dividend Policysupporting
confidence: 85%
“…The higher the total asset turnover ratio of a company, the greater the company's profit, so the amount of dividends to be distributed is also more significant. The research results support the statement's hypotheses by Firdaus and Handayani (2019) and Simanjuntak (2016), which states that total asset turnover positively and significantly affects dividend policy. Collateralizable assets are the number of assets guaranteed by the company to creditors when applying for loans.…”
Section: H2: Investment Opportunity Has a Negative Effect On Dividend Policysupporting
confidence: 85%
“…As a conclusion, the results revealed that the Current ratio (CR) and total asset turnover (TATO) showed a significant relationship to the dividend payout ratio (DPR) while debt ratio (DR) and return on investment (ROI) showed an insignificant relationship to dividend payout ratio (DPR). This finding is supported by the previous researcher which is Hadianto & Sahabuddin (2016); Gunawan and Tobing (2018); Simanjuntak (2016); Firdaus and Handayani (2019); Rizal and Triyanto (2021); Rafique (2012); Manaf et al (2021); Banarjee (2017) as well as (Fauzi and Rukmini, 2018). Future studies should focus on other variables that gives more impact towards dividend payout ratio.…”
Section: Discussionsupporting
confidence: 73%
“…This suggested that activity performance is one of the drivers of dividend policy through effective management of assets. Prior literature reports company's activity performance measured by total asset turnover positively and significantly affects the dividend policy of the company (Firdaus & Handayani, 2019;Simanjuntak, 2016;Rizal & Triyanto, 2021). However, in the other study, Arsyad et al (2021) showed that the activity performance of a company has no bearing on its dividend payout.…”
Section: Activity Ratiomentioning
confidence: 99%
“…The same result by Dewi (2013), Lindi et al (2019), and Mardiyati (2014) which states TATO has no significant effect on the DPR. This finding is contrary to stated that the DPR was significantly influenced by TATO (Firdaus and Handayani, 2019;Fuadi and Satini, 2015;Kuniawan et al, 2016;Nugroho, 2019;Purnami and Artini, 2016;Sabri et al, 2018;Simaanjuntak, 2016;Wijaya, 2017).…”
Section: Discussioncontrasting
confidence: 56%
“…In other words, a company that has a large asset circulation can reflect the magnitude of the company's ability to pay dividends, and vice versa if the circulation of assets of a small companies then the ability of dividend payments will also be small. Research that proves that the dividend pay-out ratio is influenced by the total assets turnover significantly ('Analisis Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen', n.d.;Firdaus & Handayani, 2019;Fuadi & Satini, 2015;Kuniawan et al, 2016;Purnami & Artini, n.d.;Sabri et al, 2018;Wijaya, 2017). The results of the study contradict the findings (Choridah & Diana, 2019;Mardiyati, 2014) which found no significant effect between the dividend pay-out ratio and total assets turnover.…”
Section: Introductionmentioning
confidence: 99%